Friction and wear behaviors of a gradient nano-grained AISI 316L stainless steel under dry and oil-lubricated conditions. Issue 10 (October 2018) - Wang, P.F.; Han, Z.
Abstract: A gradient nano-grained (GNG) surface layer was fabricated on an AISI 316L stainless steel (SS) by using the surface mechanical rolling treatment (SMRT). Reciprocating dry and oil-lubricated sliding tests of the GNG 316L SS in air at room temperature were conducted in comparison with the coarse-grained (CG) counterpart. Worn surface morphologies and subsurface microstructures were investigated for both 316L SS samples. 316L SS with a GNG surface layer shows a significantly improved wear resistance, especially under oil-lubricated condition. The notably wear resistance enhancement of the GNG 316L SS is attributed to the GNG surface layer with high strain accommodation ability and high hardness, which can reduce the wear volume in the running-in stage effectively.